2013
DOI: 10.1021/jp402174s
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport and Sensitized 1.5 μm Electroluminescence Properties of Full Solution-Processed NIR-OLED based on Novel Er(III) Fluorinated β-Diketonate Ternary Complex

Abstract: Solution-processed near-infrared organic light-emitting diodes (NIR-OLEDs) with structure glass/indium–tin oxide/poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate)/Er-complex/Ca/Al based on a novel Er(III) complex, [Er(tfnb)3(bipy)] (Htfnb = 4,4,4-trifluoro-1-(2-naphthyl)-1,3-butanedione and bipy = 2,2′-bipyridine) have been manufactured and their properties have been studied. A complete quenching of the organic ligand visible emission is shown, and only the sensitized 1.5 μm electroluminesce from Er(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 65 publications
5
38
0
Order By: Relevance
“…The good fitting to a singleexponential function confirms a unique and consistent coordination environment around the lanthanide ion [17]. The 4 I 13/2 lifetime obtained for the complex, s = 1.05 ls, is quite similar to other Er(III) complexes previously reported [18] and slightly lower than those reported for fluorinated b-diketonate complexes [5,6]. It is probably limited by ''second-sphere'' matrix interactions.…”
Section: Lifetime Measurementssupporting
confidence: 75%
See 1 more Smart Citation
“…The good fitting to a singleexponential function confirms a unique and consistent coordination environment around the lanthanide ion [17]. The 4 I 13/2 lifetime obtained for the complex, s = 1.05 ls, is quite similar to other Er(III) complexes previously reported [18] and slightly lower than those reported for fluorinated b-diketonate complexes [5,6]. It is probably limited by ''second-sphere'' matrix interactions.…”
Section: Lifetime Measurementssupporting
confidence: 75%
“…In previous studies [5,6] we have shown that Er(III) fluorinated b-diketonate complexes with N,N-donors can be used for low cost solution processed OLEDs, since such compounds show good processability and thin film forming properties. For NIR-OLED prototypes based on an analogous complex with 5-nitro-1,10-phenanthroline [6], we demonstrated that -upon excitation with an applied voltage -there was IR emission at 1.54 lm and a total quenching of the visible emission. In this work we describe a new ternary erbium(III) complex with ligands 3,5-heptanedione and 2,2 0 -bipiridine.…”
Section: Introductionmentioning
confidence: 99%
“…The few exceptions in which the devices successfully used the pure complexes "as-is" (deposited either by thermal deposition or from solution) involved β-diketonates with aromatic substituents which could enhance the charge transport. 4,7 In the other two devices, the NIR EL emission spectra, peaking at 1.53 µm, match very well with the PL spectra, except for a narrowing at the low-energy wing of the band. This effect is most likely related to an increase in the temperature of the material and consequently to the redistribution of the electronic population in the excited 4 I 13/2 multiplet.…”
Section: Device Properties: Electroluminescent Emission and Currentvosupporting
confidence: 54%
“…Eu-O and Eu-N distances and angles ( Table 2) are within normal ranges [26] and correspond to a distorted square antiprismatic geometry around Eu 3 þ . This type of geometry occurs frequently for trivalent lanthanide ions coordinated with diketonates [27][28][29][30][31][32][33][34]. The angle between the top and bottom square faces of the antiprism is 2.75(5)1.…”
Section: Structural Descriptionmentioning
confidence: 94%